Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1007/s11101-021-09756-2
|View full text |Cite
|
Sign up to set email alerts
|

Which East Asian herbal medicines can decrease viral infections?

Abstract: Whilst Western research for the COVID-19 crisis focuses on vaccination, in East Asia traditional herbal prescriptions are studied for SARS-CoV2 therapy. In Japan, Maoto (Ephedrae herba 4 g, Armeniacae semen 4 g, Cinnamomi cortex 3 g, and Glycyrrhizae radix 2 g, JPXVII) is used based on clinical evidence for its effect on early phase influenza (also caused by RNA viruses) comparable to that of oseltamivir. The Health Ministry of Thailand has approved Andrographis paniculata (Jap. Senshinren) extracts for treatm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 52 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Here we focus on pharmacological interventions to depression. The concept of immunity was not explicitly developed in TCM, although TCM was the first to use immunization for the control of epidemics( Kuchta et al, 2021 ). It has been shown that most herbs used in TCM have some immunomodulatory effects ( Li, 2000 ; Wu et al, 2015 ; Zhang et al, 2016 ; Zhang et al, 2020c ; Zhang and Xiao, 2021 ).…”
Section: Main Research Of Pni In Chinamentioning
confidence: 99%
“…Here we focus on pharmacological interventions to depression. The concept of immunity was not explicitly developed in TCM, although TCM was the first to use immunization for the control of epidemics( Kuchta et al, 2021 ). It has been shown that most herbs used in TCM have some immunomodulatory effects ( Li, 2000 ; Wu et al, 2015 ; Zhang et al, 2016 ; Zhang et al, 2020c ; Zhang and Xiao, 2021 ).…”
Section: Main Research Of Pni In Chinamentioning
confidence: 99%
“…In East Asian countries, such as China, Korea, Taiwan, and Japan, more than 500 common EAHM natural products are listed in each country's pharmacopeia and are still actively used as treatment agents for various acute and chronic diseases. [26][27][28][29][30] Narrowing the scope to RA, the authors investigated whether even when EAHM is used as a monotherapy, it can lead to improvement in inflammatory pain in RA based on its effects on multiple mechanisms and action pathways. [31] Integrative medicine (IM) through combination therapy with conventional intervention is a more typical approach of using EAHM for chronic intractable disorders, such as RA.…”
Section: Introductionmentioning
confidence: 99%
“…AP has the pharmacological effects of anti-inflammatory, antibacterial, antiviral, antihyperglycemic, anticancer, antistress, hepatoprotective, and immunomodulatory (Hossain et al, 2014;Panossian et al, 2021). Herbal preparations of AP have been used in many countries to treat respiratory tract infections (RTIs) (Thamlikitkul et al, 1991;Cáceres et al, 1999;Saxena et al, 2010) and colitis (Tang et al, 2011;Sandborn et al, 2013), to treat early stages of COVID-19 (Kuchta et al, 2021), and to relieve the symptoms of arthritis (Burgos et al, 2009;Hancke et al, 2019). Results of previous systematic reviews showed that, herbal preparations of AP were beneficial and safe for relieving the symptoms of RTIs and shortening time to symptom resolution (Coon and Ernst, 2004;Hu et al, 2017).…”
Section: Introductionmentioning
confidence: 99%